Analyzing electrical installation labor productivity through work sampling. Issue 4 (10th April 2017) - Hajikazemi, Sara; Andersen, Bjørn; Langlo, Jan Alexander
Abstract : Purpose: The construction industry is a labor-intensive industry, hence, the presence of labor with high productivity at each stage of the project plays a significant role in achieving project success. The purpose of this paper is to provide real-life empirical data about the current level of construction productivity, in this case electrical installation work, within construction projects in Norway. In addition, it was of interest to identify the areas which have the highest potential for improvement of labor productivity. Design/methodology/approach: This study considers the construction labor productivity through an elaboration on productive vs unproductive time within construction projects. It is based on a "frequency study" done on eight construction projects in Norway. The "work sampling" method has been used for collection of empirical data. For each project, four electricians were observed an entire working day and the amount of time they spent on performing each activity was recorded every 60th seconds. The activities observed were based on a predefined set of activities. Findings: The results of the observations show that on average, 61.1 percent of the time was direct value-added work. This number is significantly better than what is normally discussed as being productive time. However, the findings also show that there is still potential for improvement. The activities that have the highest potential for improvement include "material transfer, " "amendments to already executed installation, " "personal needs" and "waiting times." Practical implications: The study results will be of immense benefit to managers of construction projects as well as managers of construction organizations in enhancing their project performance and productivity. Originality/value: This paper contributes both theoretically and empirically to the current discussion and findings on labor productivity and its relation to project success. The results presented in this paper have important implications of labor productivity in construction projects and future studies in the area of project performance.